2009
DOI: 10.1002/bbb.180
|View full text |Cite
|
Sign up to set email alerts
|

Prospective and impacts of whole cell mediated alcoholysis of renewable oils for biodiesel production

Abstract: Biodiesel has received considerable attention during the past decade as a renewable, biodegradable and environmentally friendly fuel. There are extensive reports about immobilized lipase-mediated alcoholysis for biodiesel production and much progress has been achieved. In recent years, much attention has been paid to whole cell as the catalyst for biodiesel production. Whole cell process can be expected to reduce the biocatalyst cost considerably since separation and immobilization can be realized spontaneousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…The reaction mixture of soybean oil and methanol was circulated through a layer of a biocata lyst prepared by culturing R. oryzae in the presence of nonwoven fibrous material; after 23 hours of the reac tion under optimum conditions, the biodiesel yield was ≥70% [18]. A popular method for preparing whole cell biocatalysts is the cross linking of cell bio mass (e.g., R. oryzae) by the bifunctional agent glut araldehyde, followed by drying and the formation of granules [19][20][21][22][23]. Under optimum conditions, a high yield of Me ethers equal to 80-90% was obtained for 20 periodic reaction cycles (12 hours each).…”
Section: Biocatalysts and Methods Of Their Preparationmentioning
confidence: 99%
See 3 more Smart Citations
“…The reaction mixture of soybean oil and methanol was circulated through a layer of a biocata lyst prepared by culturing R. oryzae in the presence of nonwoven fibrous material; after 23 hours of the reac tion under optimum conditions, the biodiesel yield was ≥70% [18]. A popular method for preparing whole cell biocatalysts is the cross linking of cell bio mass (e.g., R. oryzae) by the bifunctional agent glut araldehyde, followed by drying and the formation of granules [19][20][21][22][23]. Under optimum conditions, a high yield of Me ethers equal to 80-90% was obtained for 20 periodic reaction cycles (12 hours each).…”
Section: Biocatalysts and Methods Of Their Preparationmentioning
confidence: 99%
“…The authors [18][19][20][29][30][31][32][33][34][35][36] investigated and analyzed the role of water contained both inside the biocatalysts and in the organic solvents and the gas phase. They showed that in order to achieve high activity and stability of whole cell biocat alysts, the internal water content must be optimal (5-15%); the biocatalysts in this case function as effec tively as those prepared on the basis of the extracellular (soluble) lipases.…”
Section: Biocatalysts and Methods Of Their Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, utilizing whole cell producing saponin hydrolase in which the purification and stabilization of the enzyme are not necessary instead of conventional immobilized enzyme for SB production is a potential way to reduce the biocatalyst cost, because immobilization can be carried out spontaneously during the process of cell cultivation [15]. For the best of our knowledge, there have been no reports of SB production using whole cells producing saponin hydrolase in the enzyme reaction mixture.…”
Section: Introductionmentioning
confidence: 94%